Critical Environmental Factors Affecting Learning in College of Education - Folami, Ahmadu Bolanle; Riaz, Ahmad Saeed; Musolihu, Majeed Olayori (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
Learning environment in modern day Nigeria has not been friendly with both learners and teachers and this has created a lot of vacuum in the learning process. This study discusses the critical factors affecting learning environment. This study identifies certain factors like environmental, social, intellectual that inhibit the effective participatory of students in a learning environment. The study adopted triangulate research method and about 227 participants were involved in the administration of the questionnaire for study. The data collected from the questionnaires administered were presented through frequency percentage counts. Chi-square(X2) analysis was used for testing the hypotheses to justify the outcome of the study. Our findings, shows how much learning influence environments have on the students’ success. It also reveal that students who learn in conducive environments effectively receive the adequate knowledge and performance required of them. The study concludes that critical factors such as cultural, social, environmental etc. have negative influence on the learning environment. We recommended that learning environment in nook and crannies of the world should be given appropriate facilities and attention to make it a conducive environment for learners and as well pane way for students to have freedom to express their feeling and connections of knowledge passed across by the educators.